The burden of lung cancer mortality attributable to fine particles in China - Guo, Y.; Zeng, H.; Zheng, R.; Li, S.; Pereira, G.; Liu, Q.; Chen, W.; Huxley, Rachel (Elsevier, 2017)
Although studies have examined the associations between fine particles (PM2.5) and lung cancer mortality in US and European countries, the evidence is still limited for China. In addition, no study has provided estimates of spatial variation in lung cancer mortality attributable to PM2.5 in China. In this study, we quantified the associations between lung cancer mortality and PM2.5, using a spatiotemporal model with observed data of lung cancer mortality from 75 communities from the National Cancer Registration of China from 1990 to 2009 and the annual concentrations of PM2.5 at 0.5° × 0.5° spatial resolution. We also estimated lung cancer mortality burden attributable to PM2.5 in China, with predicted county level lung cancer deaths in 2005. We found that the PM2.5-lung cancer mortality associations were non-linear, with thresholds of 40 µg/m3 overall, 45 µg/m3 for male, 42 µg/m3 for female, 45 µg/m3 for those aged 30–64 years, 48 µg/m3 for those aged 65–74 years, and 40 µg/m3 for those aged 75 years and more, above which the relative risks were 1.08 (95% CI: 1.07, 1.09), 1.07 (95% CI: 1.05, 1.08), 1.12 (95% CI: 1.1, 1.14), 1.05 (95% CI: 1.04, 1.07), 1.07 (95% CI: 1.06, 1.09), and 1.14 (95% CI: 1.12, 1.16) respectively. There were 51,219 (95% CI: 45,745–56,512) lung cancer deaths attributed to PM2.5 in 2005, with attributable fractions of 13.7% (95% CI: 12.23–15.11%) overall, 10.01% (95% CI: 8.37–11.58%) for men, 18.06% (95% CI: 15.81–20.18%) for women, 8.35% (95% CI: 6.07–10.51%) for those aged 65–74 years, 9.73% (95% CI: 7.6–11.75%) for those aged 65–74 years, 21.7% (95% CI: 19.27–23.99%) for those aged 75 years or more. In conclusion, assuming a causal relation a reduction in exposure levels of PM2.5 below thresholds would avert a substantial number of deaths from lung cancer in China.